Security Techniques for Wormhole Attack in Wireless Sensor Networks - Singh, Surinder; Singh Saini, Hardeep (International Journal of Engineering and Technology, 2018)
The wireless sensor network has group of sensors which can sense the data and route this data to base station. As there is no physical connection between sensor and base station the important data can be routed without wires. The broadcast nature of wireless sensor network makes it prone to security threat to the valuable data. The attacker node can detect the data by creating their own data aggregation and routing mechanism .The number of attacks can be possible on the network layer. Out of these attacks wormhole is one of the major attack which can change the routing method of the whole wireless sensor network. In this attack,the attacker node can control the packet transmission of whole network and route it to the tunnel of nodes. The major drawback of this attack is to increase the packet drop and disturbing the routing mechanism. A number of security techniques are developed by the researcher to reduce the packet drop ratio and secure the routing mechanism of the network. Out of all thesetechniquesfew related to packet drop ratio are discussed in this paper. TheLightweight countermeasure for the wormhole attack (LITEWORP) based on Dynamic Source routing (DSR) protocol security technique,Delay Per Hop Indication (Delphi) based on AODV(Avoidance Routing Protocol) Protocol security technique and MOBIWORP based on DSRprotocol security technique reduce the packet loss percentage 40%,43% and 35% respectively.Â Â Â